On the Use of Selected Ordination Techniques to Analyze the Parliamentary Election Results - Misztal, Małgorzata (Acta Universitatis Lodziensis. Folia Oeconomica, 2016)
Ordination techniques such as CCA (Canonical Correspondence Analysis) or RDA (Redundancy Analysis) are very popular in ecological research but almost completely unknown in, for example, socio-economic research. The goal of this paper is to concisely organize the concepts and terminology associated with ordination and to present the possibilities of its application in social research with an example of the analysis of the 2015 parliamentary elections results.